A poster guide to climate-smart agriculture - Nzuki, Esther Ndumi; Waswa, Boaz Shaban; Nderi, Alex Nduah (2025)
This poster, developed for a capacity building event with the Kimatwa Women Savings and credit cooperative group, introduces the core principles and practices of climate-smart agriculture (CSA). It outlines the three foundational pillars of CSA: sustainably increasing agricultural productivity, adapting to climate change, and reducing greenhouse gas emissions. The poster highlights key locally-relevant practices such as the use of smart seeds, agroforestry, water management, Zai pits, crop diversification, and leveraging climate information services. Emphasizing a collaborative co-design approach, the resource aims to equip farmers with the knowledge to enhance food security, build resilience against climate variability, and contribute to environmental sustainability.